Differences between low-end and high-end climate change impacts in Europe across multiple sectors - Harrison, Paula A.; Dunford, Rob W.; Holman, Ian P.; Cojocaru, George; Madsen, Marianne S.; Chen, Pei-Yuan; Pedde, Simona; Sandars, Daniel (Springer, 2018)
The Paris Agreement established the 1.5 and 2 °C targets based on the recognition “that this would significantly reduce the risks and impacts of climate change”. We tested this assertion by comparing impacts at the regional scale between low-end (< 2 °C; RCP2.6) and high-end (> 4 °C; RCP8.5) climate change scenarios accounting for interactions across six sectors (agriculture, forestry, biodiversity, water, coasts and urban) using an integrated assessment model. Results show that there are only minor differences in most impact indicators for the 2020s time slice, but impacts are considerably greater under high-end than low-end climate change in the 2050s and 2080s. For example, for the 2080s, mitigation consistent with the Paris Agreement would reduce aggregate Europe-wide impacts on the area of intensive agriculture by 21% (on average across climate models), on the area of managed forests by 34%, on water stress by 14%, on people flooded by 10% and on biodiversity vulnerability by 16%. Including socio-economic scenarios (SSPs 1, 3, 4, 5) results in considerably greater variation in the magnitude, range and direction of change of the majority of impact indicators than climate change alone. In particular, socio-economic factors much more strongly drive changes in land use and food production than changes in climate, sometimes overriding the differences due to low-end and high-end climate change. Such impacts pose significant challenges for adaptation and highlight the importance of searching for synergies between adaptation and mitigation and linking them to sustainable development goals.
Keywords: Paris agreement; High-end scenarios; Impacts; Cross-sectoral; Modelling